Development of novel, cross-species microsatellite markers for Acropora corals using next-generation sequencing technology - Shinzato, Chuya; Yasuoka, Yuki; Mungpakdee, Sutada; Arakaki, Nana; Fujie, Manabu; Nakajima, Yuichi; Satoh, Nori (Frontiers in Marine Science, 2014)
The genus Acropora (Scleractinia, Acroporidae) is one of the most widespread coral genera, comprising the largest number of extant species among scleractinian (reef-building) corals. Molecular phylogenetic studies have suggested that A. tenuis belongs to the most basal clade (clade I) while A. digitifera belongs to a derived clade (clade IV). In order to develop microsatellite markers that would be useful for most Acropora species, we sequenced the genomic DNA of A. tenuis, using a next generation sequencer (Illumina MiSeq), and designed primer sets that amplify microsatellite loci. Afterward we selected primer pairs with perfectly matched nucleotide sequences from which at least one primer was uniquely mapped to the A. digitifera genome. Fourteen microsatellite markers showed non-significant departure from Hardy–Weinberg equilibrium (HWE) in both A. tenuis and A. digitifera. Thus these markers could be used for wide range of species and may provide powerful tools for population genetics studies and conservation of Acropora corals.